Medicinal chemistry of histone deacetylase inhibitors - Ružić, Dušan; Djoković, Nemanja; Nikolić, Katarina; Vujić, Zorica (Archives of Pharmacy, 2021)
Today, we are witnessing an explosion of scientific concepts in cancer chemotherapy. It has been considered for a long time that genetic instability in cancer should be treated with drugs that directly damage the DNA. Understanding the molecular basis of malignant diseases shed light on studying phenotypic plasticity. In the era of epigenetics, many efforts are being made to alter the aberrant homeostasis in cancer without modifying the DNA sequence. One such strategy is modulation of the lysine acetylome in human cancers. To remove the acetyl group from the histones, cells use the enzymes that are called histone deacetylases (HDACs). The disturbed equilibrium between acetylation and deacetylation on lysine residues of histones can be manipulated with histone deacetylase inhibitors (HDACi). Throughout the review, an effort will be made to present the mechanistic basis of targeting the HDAC isoforms, discovered selective HDAC inhibitors, and their therapeutical implications and expectations in modern drug discovery.